2020
DOI: 10.13057/biodiv/d211237
|View full text |Cite
|
Sign up to set email alerts
|

Field test on the palatability of the subterranean termites to pine wood with various treatments

Abstract: Abstract. Ariana, Fannani AR, Nandika D, Haneda NF. 2020. Field test on the palatability of the subterranean termites to pine wood with various treatments. Biodiversitas 21: 5763-5771. One of the keys to successfully determining the subterranean termite species' diversity in an area is using wood samples of their preference. This research aimed to evaluate the palatability of the subterranean termites to pine wood (Pinus merkusii) with boiling, steaming, hot vapor pressure, and oven treatments in the Arboretum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
6
2
Order By: Relevance
“…According to the Indonesian Soil Research Institute ( 2009), the low-medium group classified the C-organic content. The C-organic content at the test site was higher than in the study site of Arinana et al (2020), ranging from 0.69%-1.78%, with the test site in the form of settlements. According to Mahaney et al (1999), termites play a role in increasing organic matter in the soil and is also supported by Jiménez and Decaëns (2006), stating that increased organic matter was obtained from the feces and excretion of termite saliva, which is the main component in building nests.…”
Section: Soil Characteristics Analysiscontrasting
confidence: 55%
See 1 more Smart Citation
“…According to the Indonesian Soil Research Institute ( 2009), the low-medium group classified the C-organic content. The C-organic content at the test site was higher than in the study site of Arinana et al (2020), ranging from 0.69%-1.78%, with the test site in the form of settlements. According to Mahaney et al (1999), termites play a role in increasing organic matter in the soil and is also supported by Jiménez and Decaëns (2006), stating that increased organic matter was obtained from the feces and excretion of termite saliva, which is the main component in building nests.…”
Section: Soil Characteristics Analysiscontrasting
confidence: 55%
“…Bogor (Arinana et al, 2020), and Jakarta . Peralta et al (2004) 46.40"E, 6° 33' 27.22"S; 106° 43' 46.17"E, 6° 33' 27.32"S; 106° 43' 46.11"E, 6° 33' 27.80"S, and 106° 43' 46.43"E, 6° 33' 27.74"S. The wood baits were buried until 25 cm of the total length of the wood was vertically immersed under the ground and the upper half of above ground the wood bait are and marked (Arinana et al, 2020). The distance between the wood bait in the longitudinal direction (row) was -461 -30 cm, while the distance between the wood bait in the wide direction (column) was 60 cm.…”
Section: Introductionmentioning
confidence: 99%
“…Termite specimens found in residential testing sites are similar to the research of Arinana et al (2020a), who found four species of subterranean termites attacking wood samples in Sinarsari Nature housing, namely, Macrotermes sp., Microtermes sp., Schedorhinotermes sp., and Odontotermes sp. Meanwhile, the specimens in the arboretum testing site are slightly different from the research of Arinana et al (2020b) and Arinana et al (2022), who found Capritermes sp. specimen on the Bogor Agricultural University arboretum testing site.…”
Section: Termite Species That Attack Wood Samplecontrasting
confidence: 63%
“…Baiting method: baits were placed within termite observation stations. The bait is made of a PVC tube (20 cm diameter, 25 cm length; Figure 2) buried halfway into the ground (Arinana et al 2020). Three pine wood stakes (Pinus merkusii Jungh.…”
Section: Collection Of Termitesmentioning
confidence: 99%
“…Baits containing cellulose that subterranean termites prefer are required to determine the diversity of termite species in an area. Wood is one of the most easily accessible cellulose-containing materials (Arinana et al 2020).…”
Section: Introductionmentioning
confidence: 99%